Lymphocytic Airway Inflammation in Lung Allografts - Santos, Jesse; Calabrese, Daniel R.; Greenland, John R. (Frontiers in Immunology, 2022)
Lung Transplant remains a key therapeutic option for patients with end stage lung disease but short- and long-term survival lag other solid organ transplants. Early ischemia-reperfusion injury in the form of primary graft dysfunction (PGD), and acute cellular rejection are risk factors for chronic lung allograft dysfunction (CLAD), a syndrome of airway and parenchymal fibrosis that is the major barrier to long term survival. An increasing body of research suggests lymphocytic airway inflammation plays a significant role in these important clinical syndromes. Cytotoxic T cells are observed in airway rejection, and transcriptional analysis of airways reveal common cytotoxic gene patterns across solid organ transplant rejection. Natural killer (NK) cells have also been implicated in the early allograft damage response to PGD, acute rejection, cytomegalovirus, and CLAD. This review will examine the roles of lymphocytic airway inflammation across the lifespan of the allograft, including: 1) The contribution of lymphocytes to PGD and the impact of PGD on the adaptive immune response. 2) Acute cellular rejection pathologies and the potentially underrecognized significance of airway inflammation. 3) Potentiators of airway inflammation and heterologous immunity, such as respiratory infections, aspiration, and the airway microbiome. 4) Airway contributions to CLAD pathogenesis, including epithelial to mesenchymal transformation, club cell loss, and the evolution from constrictive bronchiolitis to parenchymal fibrosis. 5) Protective mechanisms involving regulatory T cells. In summary, this review will examine our current understanding of the complex interplay between the transplanted airway epithelium, lymphocytic airway infiltration, and rejection pathologies.